Das globale Huhn - Petschow, Ulrich; Idel, Anita (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2004)
The loss of agrobiodiversity is an upcoming field on international policy agendas. The case study “global chicken” reveals the causes of the loss of agrogenetic resources of chicken. This loss is caused by agricultural research linked with economic interests and property right systems as well as the enforcement of a fordist production model in the agricultural sector with immense distributional effects especially on agrogenetic resources. The hybrid chicken breeding industry destroys genetic resources by “outcompeting” traditional breeding systems.